Analisis Praktik Klinik Dengan Intervensi Inovasi Terapi Position Lateral Dan Suction Terhadap Hemodinamik Pasien Stroke Hemoragik Post Op Craniotomy Diruang Icu RSUD A.M Parikesit Tenggarong : Studi Kasus - Taharuddin Taharuddin; Faramita Kumala Sari; Annaas Budi Setwayan; Alfi Ari Fahkrur Rizal (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Introduction: Hemorrhagic stroke is a type of stroke that has a high mortality rate and disability, especially in patients who require craniotomy. Postoperatively, patients generally experience impaired consciousness and an inability to maintain the airway effectively, which can have an impact on hemodynamic instability. Therefore, innovative interventions such as Lateral Position and Suction (mucus suction) are important in supporting the stability of the patient's condition in the Intensive Care Unit (ICU). Objective: To analyze clinical practice with innovative interventions of Lateral Position and Suction therapy of hemodynamic status of hemorrhagic stroke patients after craniotomy surgery in the ICU of A.M. Parikesit Tenggarong Hospital. Methods: This study used a case study approach in post op craniotomy hemorrhagic stroke patients who were treated in the ICU, with nursing interventions in the form of Lateral Position and Suction according to the protocol. Evaluation was carried out by observing changes in hemodynamic parameters before and after the intervention, including blood pressure, pulse, respiratory rate, and oxygen saturation. Results: Lateral Position and Suction showed significant improvements in the patient's hemodynamic status, especially in increased oxygen saturation, blood pressure stability, and decreased accumulation of secretions in the airway. Conclusion: Lateral Position and Suction Therapy is effective in improving the hemodynamic stability of postcraniotomy hemorrhagic stroke patients. This intervention can be used as one of the independent nursing measures in the management of critical patients in the ICU room.